Analisis Kebugaran Jasmani Siswa Melalui Tes Lari 1000 Meter Siswa Kelas 5 SDN Pojok 2 Kota Kediri - Dewi Yuliana; Mohammad Nur Kholis; Ahmad Zakiyyunnuhaa (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to determine the physical fitness level of fifth-grade students at SDN Pojok 2 Kota Kediri through a 1000-meter running test. A descriptive quantitative approach was used with a total sample of 30 students, consisting of 17 boys and 13 girls. The results showed that most students fell into the "poor" and "very poor" fitness categories. Male students were mostly in the "poor" category (47.1%) with an average time of 6.21 minutes, while female students were predominantly in the "very poor" category (76.9%) with an average time of 10.2 minutes. Only a few students reached the "fair" and "good" categories, and none achieved the "very good" category. These findings indicate that students’ physical fitness, especially cardiovascular endurance, is still low. Therefore, a structured, enjoyable, and inclusive fitness program is necessary to enhance student participation, particularly among girls. This study is expected to serve as a reference for PE teachers and schools in designing effective and sustainable strategies to improve students’ physical fitness.